An elevated gain DC-DC converter with active switched inductor for PV application - Kalarathi Mahalingam; Gnanavadivel Jothimani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Innovative power electronic converters have emerged because of renewable energy expansion in the past two decades. Direct current DC grids can operate independently or connected to power grids. A DC grid has distributed generation (DG) units, such as solar panels and, fuel cells. It is necessary to have a DC-DC converter in DC grids to raise output voltage. Boost converters have limited voltage gain, and their switching stress is often equal to their output voltage. This work proposes a converter which gives high gain and less stress when compared to other recent converters. At 0.8 duty ratio, this converter produces an elevated gain of 59. An experimental prototype is built for the proposed converter and the results are presented.